EFEKTIVITAS MODEL PEMBELAJARAN CPA BERBASIS MEDIA BLOK DIENES TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS III SDN 5 KESU’ - Fenny Paonganan; Novalia Sulastri; Reni Lolotandung (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Abstract This study aims to determine the effectiveness of the Concrete-Pictorial-Abstract (CPA) learning model based on Dienes Block media on the mathematical problem-solving ability of third-grade students at SDN 5 Kesu'. This research is a quantitative study with a pre-experimental design (one-group pretest-posttest design). The population as well as the sample of this study were all 24 third-grade students at SDN 5 Kesu', selected using the saturated sampling technique. The data collection instrument was a mathematical problem-solving ability test consisting of 18 valid and highly reliable essay items (a = 0.888). Data analysis techniques utilized descriptive and inferential statistics. The hypothesis testing using the paired sample t-test showed a significance value of Sig. (2-tailed) = 0.000 < 0.05, indicating a highly significant difference in the students' mathematical problem-solving abilities before (pretest) and after (posttest) the intervention. Thisimprovement is also supported by an average N-gain score of 0.51, which falls into the "moderate" category. Based on these results, it can be concluded that the implementation of the CPA learning model based on Dienes Block media is effective in improving the mathematical problem-solving ability of third-grade students at SDN 5 Kesu'.